Achieving healthy and sustainable food environments for all - Fan, Shenggen (2019)
Food is critical to human and planetary health, yet food is currently threatening both people and planet. World hunger is on the rise - from 784 million people in 2014 to 821 million in 2017, millions of children remain stunted and nearly 2 billion adults are overweight or obese (FAO et al., 2017; Development Initiatives, 2017). Moreover, food systems – which include all actors and sectors involved in producing, distributing, retailing and consuming food – are at the centre of many environmental challenges facing the planet. Nearly 85 percent of global water use goes to agricultural irrigation, of which 15–35 percent is unsustainable, while close to a quarter of all global land is degraded (IFPRI, 2012; Rosengrant et al., 2009). Agriculture and food systems contribute up to 29 percent of all greenhouse gas emissions (Vermeulen et al., 2012). Overall, food systems are pushing planetary boundaries in terms of greenhouse gas emissions, resource use and degradation. If crossed, this could generate abrupt or irreversible environmental changes (Rockström et al., 2009). However, it is possible to feed the world’s growing population a healthy, diverse and nutritious diet within our natural boundaries (Willett et al., 2019). To do so, these types of food must be available and accessible where people acquire and consume food – in their food environments. Food environments are the range of food sources, activities and products that surround people in their everyday lives. They are the interface between consumers’ food acquisition and consumption and the wider food system, encompassing dimensions such as the availability, accessibility, affordability, desirability, convenience, marketing and properties of food sources and products (Turner et al., 2017). This is why we should aim to achieve healthy and sustainable food environments.